To the lighthouse. (2nd February 2021) - Harries, Judith
Abstract : Mr Grinling is probably one of the most famous lighthouse keepers in the world, brought to life by Ronda Armitage in her series of classic children's books. There are lots of ways to use them to explore peoples' occupations and life-styles.